PENATAAN ZONING INTERIOR RUMAH PAJANG UPAYA MENGOPTIMALKAN OMSET HASIL KERAJINAN LOGAM DI TUMANG, BOYOLALI - Sunarmi -; Dharsono -; Ahmad Fajar Ariyanto (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2009)
This research is entitled â€œInterior Zoning Layout of Pajang House An Attempt of Optimizing the Sale of Metal Craft Result in Tumang-Boyolali Central Javaâ€. The objective of research is to find the solution of interior design offer as residence and as the display. The attempt of supporting the tourism area in the village Tumang, Boyolali. This research is using descriptive qualitative methods The approach employed was phenomenological one supported by the psychological, ergonomic, social and cultural approaches, based on the purposive sampling. The data source employed includes: the source, place and event, metal works, craftsmenâ€™s personal note. Technique of collecting data employed was interview, observation and library study. The data accuracy and validity employed was source triangulation technique. The analysis model borrowed the interactive one. Tumang society live in the Javanese traditional concept. They are attached in the close relationship and the environment establishes the strong sense of brotherhood that affects their taste and view on the house shape. The residence layout prioritizes more the societyâ€™s interest rather than their business. There are two factors affecting the craftsmen who do not display their works properly. The internal factor: the less skill about the display house design. The external factor: the less number of visitors visiting routinely the village Tumang. To cope with the problem the craftsmen,need an activity in the form of workshop for an environment as the model, leads to the attempt of expanding the information about the existence of a metal craftsmen group in Tumang to the public, through the shape processing in several strategic places. The house physical imaging uses the consumer profession behavior theme approach strategy that will become the attraction in the design solution. The display house physical imaging was done by processing the display shape of crafting product through the wall display playing.Keywords: Zoning, display house, profession behavior